The Preventive Role of Criminal Law in Preventing Communal Violence in Post-Conflict Societies - Dr.Batool Ibrahim Abdulrahman; Dr. Aseen Ahmed Fakhri (Indonesian Journal of Law and Economics Review, 2026)
General Background: Communal violence remains a major threat to stability and sustainable peace in post-conflict societies, where unresolved identity-based grievances persist despite the cessation of armed conflict. Specific Background: Criminal law, traditionally punitive, is increasingly conceptualized as a preventive mechanism aimed at deterring collective violence, criminalizing incitement, and reinforcing individual accountability within fragile post-conflict environments. Knowledge Gap: There is a disconnection between the theoretical preventive capacity of criminal law and the practical limitations arising from weak institutions, selective enforcement, and tensions with transitional justice mechanisms. Aims: This study examines how criminal law contributes to the prevention of communal violence and identifies the structural and institutional constraints that limit its preventive capacity. Results: The findings indicate that criminal law can establish normative boundaries, deter violence through punishment, and promote individualized responsibility; however, its preventive function is conditional upon institutional independence, procedural fairness, legal certainty, and public trust, while being undermined by institutional fragility, lack of legitimacy, and competing transitional justice priorities. Novelty: The study integrates doctrinal and interdisciplinary perspectives to position criminal law as both a normative and institutional preventive tool within post-conflict governance. Implications: Criminal law should be incorporated into broader peace-building strategies that combine accountability, reconciliation, and institutional strengthening to reduce the recurrence of communal violence and support long-term rule of law. Highlights:• Establishes legal boundaries distinguishing collective violence from lawful expression• Demonstrates conditional deterrence dependent on institutional credibility and fairness• Identifies structural barriers including weak enforcement and legitimacy deficits Keywords: Criminal Law, Communal Violence, Post Conflict Societies, Preventive Justice, Rule Of Law